Results of the Global Burden of Disease study for schizophrenia: trends from 1990 to 2021 and projections to 2050 - Zhan, Zhonghua; Wang, Jiaming; Shen, Tongping (Frontiers in Psychiatry, 2025)
IntroductionSchizophrenia represents a substantial aspect of the overall burden associated with mental disorders and ranks as the third leading cause of disability worldwide.MethodsUtilizing data from the Global Burden of Disease (GBD), Injury, and Risk Factors Study, this research examines global trends in the prevalence, incidence, and disability-adjusted life years (DALY) attributable to schizophrenia, with stratification by age, sex, and socio-demographic index (SDI).ResultsBetween 1990 and 2021, the prevalence of schizophrenia increased from 13.62 million to 23.18million, the incidence rose from 883,000 to 1.223 million, and the age-standardized disability rate (ASDR) escalated from 8.76 million to 14.82 million, reflecting increases of over 70.1%, 38.5%, and 69.2%, respectively. However, global age-standardized estimates have remained relatively stable. The male-to-female burden ratio for schizophrenia in the general population has shown consistency over the past three decades, with men exhibiting a higher risk compared to women. As regional life expectancy continues to improve, an increase in the burden of schizophrenia is anticipated.DiscussionNotably, the burden is more pronounced in economically stable, high-income countries within high SDI regions, while it is exacerbated in low SDI regions due to inadequate health policies. Projections indicate that the prevalence, incidence, and overall burden of schizophrenia will continue to rise through 2050. Consequently, policymakers across all nations should revise existing policies and implement measures, including the establishment of comprehensive systems for early diagnosis and efforts to mitigate the stigma associated with schizophrenia, to proactively address the anticipated increase in the disease’s burden.